A comparative analysis of multicultural perspectives on leadership competencies and organizational capabilities required for competitiveness in the 1990's - Ready, Douglas A. (Cranfield University, 1992)
This thesis considers three main arguments. -First, that managersfrom different cultural orientations tend to look at competitive, organizational and leadership challenges differently due to their cultural orientation or "mapping". Second, that even though it appears that, managers,, from various cultures may have different cultural maps, it is-possible to find a "muld cultural common ground" concerning the organizational capabilities and leadership competencies perceived as critical for competitiveness in the 90's. And third, that a perceived challenge facing senior managers in the 90's is managing the tensions and processps of transformation and change resulting from attempts to develop a shared meaning of the company's vision, balanced by an operating culture that encourages substantial differences in perspectives. The introduction provides a rationale for the importance of the topic and explores this researcher's interest in the subject. It also provides the foundation for definitions and operating terms for a number of the words or phrases that are used throughout the text. , The' review, of the literature examines both the general breadth of this researcher's reading program that served as preparation for the study, as well as a look at the works that served as important foundations for the focal points of this research. It also explains how the literature influenced the research methods. The thesis arguments provide the main questions that are examined in the research and includes the backgrounds and premises for selecting these arguments. The value and benefits of the research are also examined here. The research methodologies chapter details in depth the processes used to conduct the research, provides the linkages between the methods and the literature and explores the use of analytical tools and frameworks in the study of managerial perceptions. The results chapter presents the main findings of the research and explains how these findings support the thesis arguments. A subsequent discussion of these results, their linkage to the literature and an explanation of their meaning is discussed in the next chapter. Finally, the main lessons of the research, the value of the methodologies, the implications of the research for practicing managers and researchers and suggestions for additional research are explored in the conclusions. While the statistical procedures'are explained in great depth, many of the actual data tables and detailed findings, as well as the questionnaire used may be found in the appendices.